TRAINING OF FUTURE SPEECH THERAPISTS FOR THE USE OF COMPUTER TECHNOLOGIES IN PROFESSIONAL ACTIVITIES - Mariia KOMISARYK; Kateryna KUZNIETSOVA; Yaryna TANIAVSKA (Association of Social and Educational Innovation, 2024)
The article describes the methodology of professional training of future future speech therapists for the use of computer technologies in professional activities, which involves a consistency of stages, where the content of educational disciplines from the cycle of professional and practical training is adjusted at the preparatory stage; activation of independent search of students; at the theoretical level - the introduction of an additional special course "Computer games in the work of a speech therapist"; the practical stage provides the transfer of acquired knowledge, practical abilities and skills to various types of pedagogical practice throughout the entire period of study in high school, as well as the productive stage.